Bax Expression of Throphoblast Cells did not Differ between Early and Late Onset Preeclampsia: Ekspresi Bax Sel Trofoblas tidak Berbeda antara Preeklamsia Awitan Dini dan Lanjut - Dewajani Purnomosari; Made Ariyana; Diah R. Hadiati; Irwan T. Rachman (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: To compare Bax protein expression in throphoblast cells of early and late onset PE. Methods: A cross sectional study involving 36 cases of early onset PE and 36 cases of late onset PE was conducted. Bax protein expression was evaluated from sample of placental tissue collected from the study population and calculated using H-Score. Data on age, number of parity, gestational age, body mass index was collected from the medical records. Expression of Bax was compared using Mann-Whitney test. Results: There was no difference in the clinical characteristics (age, number of parity, BMI, SBP, DBP, and MAP) between the two groups. There was no difference in the expression of Bax protein between the early and late onset PE (mean H-score early vs. late onset PE: 1.48 vs 1.46, p=0.814, Mann Whitney U test). Clinical characteristics of the study population also did not correlate with the Bax expression (R for number of parity: 0.052, age: 0.009, gestational age: -0.014, BMI: 0.063, all p values were >0.05, linear regresion). Conclusion: There is no difference in the expression of Bax protein of throphoblast cells between early and late onset PE. Keyword: apoptosis, BAX, early onset, late onset, preeclampsia Abstrak Tujuan: Untuk membandingkan ekspresi protein Bax dalam sel trofoblas pada preeklamsia (PE) onset dini dan lambat. Metode: Sebuah studi potong lintang yang melibatkan 36 kasus PE onset dini dan 36 kasus PE onset lambat dilakukan. Ekspresi protein Bax dievaluasi dari sampel jaringan plasenta yang dikumpulkan dari populasi studi dan dihitung menggunakan skor-H. Data usia, jumlah paritas, usia kehamilan, indeks massa tubuh dikumpulkan dari rekam medis. Ekspresi Bax dibandingkan menggunakan uji Mann-Whitney. Results: Tidak terdapat perbedaan pada karakteristik klinis (usia, jumlah paritas, IMT, TDS, TDD, dan MAP) antara kedua kelompok. Tidak terdapat perbedaan dalam ekspresi protein Bax antara PE onset dini dan lambat (rata-rata H-skor PE onset dini dan lambat: 1.48 vs 1.46, p = 0.814, uji Mann Whitney U). Karakteristik klinis populasi studi juga tidak berkorelasi dengan ekspresi Bax (R untuk jumlah paritas: 0,052, usia: 0,009, usia kehamilan: -0,014, BMI: 0,063, nilai p dari semua variable tersebut adalah sebesar >0,05, dengan menggunakan regresi linier). Kesimpulan: Tidak terdapat perbedaan dalam ekspresi protein Bax pada sel trofoblas antara PE onset dini dan lambat. Kata kunci: apoptosis, BAX, onset dini, onset lambat, preeklamsia